'Sekolah Cepat Edukasi Hukum Media Sosial': Education Prevention, Supervision and Enforcement of Crimes of Hate Speech through Social Media - Manihuruk, Nandri Kanisius (Universitas Negeri Semarang, 2018)
Crimes of hate speech on social media are the impact of so many social media users in Indonesia and the public's ignorance of the legal limits of media, therefore the authors make scientific works of school legal education social education (Sekolah Cepat Edukasi Hukum Media Sosial, or SEPAT KASIH SOSIAL MEDIA) (education of prevention, supervision and enforcement Crimes of hate speech through social media). SEPAT KASIH SOSIAL MEDIA is a legal education program whose teaching and learning activities do not take a long time, which is only about one to two semesters, in this program three things that must be possessed by every student are teaching about the offense of hate speech, service Society in the form of socialization, education and presentation and finally is research related to the pursuit of hate speech and scientifically studied.